The feasibility and acceptability of mass drug administration for malaria in Cambodia: a mixed-methods study. (16th June 2018) - Peto, Thomas J; Tripura, Rupam; Sanann, Nou; Adhikari, Bipin; Callery, James; Droogleever, Mark; Heng, Chhouen; Cheah, Phaik Yeong; Davoeung, Chan; Nguon, Chea; von Seidlein, Lorenz; Dondorp, Arjen M; et al.
Abstract: Background: Mass drug administrations (MDAs) are part of the World Health Organization's Plasmodium falciparum elimination strategy for the Greater Mekong Subregion (GMS). In Cambodia, a 2015–2017 clinical trial evaluated the effectiveness of MDA. This article explores factors that influence the feasibility and acceptability of MDA, including seasonal timing, financial incentives and the delivery model. Methods: Quantitative data were collected through structured questionnaires from the heads of 163 households. Qualitative data were collected through 25 semi-structured interviews and 5 focus group discussions with villagers and local health staff. Calendars of village activities were created and meteorological and malaria treatment records were collected. Results: MDA delivered house-to-house or at a central point, with or without compensation, were equally acceptable and did not affect coverage. People who knew about the rationale for the MDA, asymptomatic infections and transmission were more likely to participate. In western Cambodia, MDA delivered house-to-house by volunteers at the end of the dry season may be most practicable but requires the subsequent treatment of in-migrants to prevent reintroduction of infections. Conclusions: For MDA targeted at individual villages or village clusters it is important to understand local preferences for community mobilisation, delivery and timing, as several models of MDA are feasible.